Die karakterisering van Natanael in die Johannesevangelie - Hunt, Steven (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
The characterization of Nathanael in the Gospel of John In this article the characterization of Nathanael is investigated by taking into account both historical concerns and literary aspects. After a brief discussion of questions pertaining to Nathanael’s identity and historicity, his basic characterization is discussed. Following this, a number of important issues are investigated in more detail, namely the way in which the introduction of this character on the fourth day can be related to the cosmological setting in the Gospel; the suggestion that Nathanael is portrayed as a follower of the Baptist and gift of God; an exploration of the intercharacterizational relationship of Nathanael and Simon Peter; and, finally, an investigation of the intertextual relationships between the Nathanael episode and Zechariah 3:10 (in particular, the notions of the “Branch” and “under the fig tree”).